2022
DOI: 10.1111/1460-6984.12778
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic deficits in patients with schizophrenia and right hemisphere damage: A pilot study

Abstract: Background While pragmatic deficits are well documented in patients with schizophrenia (SCZ) and right hemisphere damage (RHD), there is a paucity of research comparing the pragmatic deficits of these two groups. Do they experience similar cognitive dysfunction or is there a dissociation between the two patient groups? Aims To investigate the nature of pragmatic deficits in these two groups and to gain an understanding of the underlying cognitive mechanisms that might be associated with these deficits to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 193 publications
0
2
0
Order By: Relevance
“…Our results showed that RBD patients performed lower as a group in pragmatic tests compared to the control group. Therefore, the results confirm previous studies, which have shown that RBD patients exhibit communicational deficits [22,48]. A further case-bycase investigation revealed that not all patients demonstrate pragmatic impairments, a finding that verifies the heterogeneity of the patients in terms of communication deficits, a result that has been previously suggested [20,30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that RBD patients performed lower as a group in pragmatic tests compared to the control group. Therefore, the results confirm previous studies, which have shown that RBD patients exhibit communicational deficits [22,48]. A further case-bycase investigation revealed that not all patients demonstrate pragmatic impairments, a finding that verifies the heterogeneity of the patients in terms of communication deficits, a result that has been previously suggested [20,30].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, subjects 1 and 11 should be studied separately due to their low similarity with the other two clusters. The second cluster consists of ten patients (2,6,20,19,4,10,22,14,21,12). In this cluster, the patients exhibit mainly ToM deficits, specifically in the affective facet of the non-verbal test, besides patient 10 who exhibits deficits in three subcomponents from the two ToM tests, with some also presenting impairment in executive functions, specifically in the processing speed.…”
Section: The Outcome Of the Case-by-case Investigation Is Shown In Tablementioning
confidence: 99%
See 1 more Smart Citation
“…132 Preliminary data suggest that the test battery holds promise for a transdiagnostic approach toward pragmatic deficits across clinical populations. 134 Adaptation of such test batteries might help create a relatively homogenous data set for researchers to better understand the nature of language breakdown in different types of clinical populations, in general, and dementia, in particular, as well as its cultural and language-specific variations. Deeper insights may lead us to a more precise and effective diagnostic tool.…”
Section: Future Directionmentioning
confidence: 99%
“…Ten different subtests cover different aspects of pragmatic skills: (a) conversational pragmatics; (b) comprehension of abstract words in sentence context; (c) comprehension of ambiguous words in sentence context; (d) comprehension of figurative speech; (e) narrative and interpretive skill, (f) discourse comprehension, (g) comprehension of inferred meaning; (h) comprehension of emotional expressions; (i) gesture comprehension; and (j) humor comprehension. Moreover, “open‐ended questions and a naturalistic method of elicitation (verbal explanation) make the battery an ideal tool to explore the diverse minds of a diverse population.” 132 Preliminary data suggest that the test battery holds promise for a transdiagnostic approach toward pragmatic deficits across clinical populations 134 . Adaptation of such test batteries might help create a relatively homogenous data set for researchers to better understand the nature of language breakdown in different types of clinical populations, in general, and dementia, in particular, as well as its cultural and language‐specific variations.…”
Section: Future Directionmentioning
confidence: 99%